2016
DOI: 10.1016/j.nicl.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

The application of a mathematical model linking structural and functional connectomes in severe brain injury

Abstract: Following severe injuries that result in disorders of consciousness, recovery can occur over many months or years post-injury. While post-injury synaptogenesis, axonal sprouting and functional reorganization are known to occur, the network-level processes underlying recovery are poorly understood. Here, we test a network-level functional rerouting hypothesis in recovery of patients with disorders of consciousness following severe brain injury. This hypothesis states that the brain recovers from injury by resto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 82 publications
(109 reference statements)
7
44
0
Order By: Relevance
“…While Nakamura and colleagues (2009) showed a reduced small world index in severe TBI patients (at timepoint 1), Kuceyeski et al (2016) revealed a higher small world index in severe TBI patients. Moreover, Hillary et al (2014) showed a marginally significant group difference in small worldness, and the studies by Caeyenberghs et al (2012) and Messé et al (2013) failed to observe any significant group differences on small-world metrics.…”
Section: Graph Metrics Alterations In Tbi 41 Small-world Propertiesmentioning
confidence: 93%
See 4 more Smart Citations
“…While Nakamura and colleagues (2009) showed a reduced small world index in severe TBI patients (at timepoint 1), Kuceyeski et al (2016) revealed a higher small world index in severe TBI patients. Moreover, Hillary et al (2014) showed a marginally significant group difference in small worldness, and the studies by Caeyenberghs et al (2012) and Messé et al (2013) failed to observe any significant group differences on small-world metrics.…”
Section: Graph Metrics Alterations In Tbi 41 Small-world Propertiesmentioning
confidence: 93%
“…Given the different etiologies (other than TBI only) discussed in several surveyed studies (Arnemann et al, 2015;Gratton et al, 2012;Kuceyeski et al, 2016;Nomura et al, 2010) and the significant pathophysiological differences between mild and moderate-to-severe TBI, we should not generalize functional connectivity findings across etiologies of ABI and injury severities. Subgroup analyses could be performed, whereby each type of injury (focal contusion, diffuse axonal injuries, axonal degeneration) could be examined in detail, investigating the extent to which graph metrics are preserved or affected by each type of injury.…”
Section: Methodological Considerations and Future Studiesmentioning
confidence: 99%
See 3 more Smart Citations